ENSINO DO FENÔMENO RELIGIOSO NA ESCOLA PÚBLICA: área de conhecimento necessária para uma sociedade secularizada - LAGES, Jose Antonio Correa (2016)
Studying the historical evolution and taking an overview of the religious education in Brazil, we today face the problem of the exclusion of two different types of view on its treatment on public schools: or should it exist the "confessional" religious teaching, or it shouldn't exist at all. Overcoming the view of the laicity as an abstention when affirming that the religious, on its own definition, doesn't concern us nor even the science, and admitting a laicity of intelligence when we defend that is our duty or even the duty of science to understand it as a human and social expression, the teaching of the religious phenomenon can overcome these two views with the use of a strong epistemological basis for this area of knowledge, as fixed in our Constitution. It guarantees the respect to the diversity and the cultural plurality of the brazilian society and it contributes to the comprehension of the religious phenomenon as a "cultural object". It is capable of support practices of a teaching of the religious phenomenon in a secular education system, without prejudicing its laicity - on the contrary, it can actually go on its behalf. The secular education focusing on the formation of a citizen cannot ignore the existance of religions for its strong presence and for its role in a society. It is needed to critically decrypt the religions representations and its practices in name of a more constructive cohabitation between people and extract values from the religious traditions that can contribute with the human life on its plenitude. This model of teaching the religion as an anthropological, social and cultural phenomenon can even perform a specific role on what concerns the knowledge of oneself (identity) and also on what regards the acceptation of the different (alterity), pointing to the construction of ethic values and the notion of being a citizen. This research is based on a great bibliographic raising data and interviews with specialists on secularization, laicity and on religious teaching, all based on Régis Debray's proposal adopted in France. It leads us to conclude that the teaching of the religious phenomenon in Brazil's public schools is not only necessary, but indispensable if we want an education that contributes to the formation of our students in a solidary living.